Drug-coated balloon angioplasty versus conventional angioplasty for symptomatic non-acute intracranial artery occlusion - Dong, Kaiyue; Chen, Yingkun; Song, Yun; Sun, Lili; Zheng, Meimei; Yin, Hao; Zhang, Jun; Li, Shuoshuo; Yin, Tianxi; Wang, Wei; Meng, Yao; Li, Weili; et al. (Frontiers in Neurology, 2025)
Background and objectiveNon-acute intracranial artery occlusion (ICAO) is an important cause of recurrent ischemic stroke despite aggressive medical treatment. Conventional angioplasty has high incidences of perioperative complications and restenosis in treating these patients. Drug-coated balloon (DCB) treatment has shown superiority in preventing restenosis. This study aimed to compare the DCB angioplasty with conventional angioplasty in symptomatic ICAO patients.MethodsFrom January 2016 to March 2024, consecutive patients with symptomatic non-acute ICAO treated with endovascular therapy were enrolled and dichotomized by whether DCB was used. Propensity score matching analysis was used to compare the perioperative complications, clinical and imaging follow-up results of the two groups.Results158 eligible patients were included in this study. There were 104 cases in the DCB group and 54 cases in the non-DCB group. A total of 92 matched patients were selected for propensity score matching analysis. At 6 months follow-up, the median stenosis degree (19.3% [0% 34.3%] vs. 43.6% [22.8% 80.2%], p = 0.009) and total restenosis incidence (10.9% [5/46] vs. 39.1% [18/46], p = 0.004) were significantly lower in the DCB group. There were no statistically significant differences in the incidences of perioperative complications (8.7% vs. 17.4%, p = 0.388), symptomatic restenosis (2.2% vs. 8.7%, p = 0.375) and recurrent ischemic events (4.3% vs. 10.9%, p = 0.453) between the two groups.ConclusionIn patients with symptomatic non-acute ICAO, compared with conventional angioplasty, DCB angioplasty can effectively reduce the restenosis degree and restenosis risk.